Gestión de inventarios en la empresa Representaciones Soria del cantón Babahoyo - Sánchez Peña, Jianella Jazmín (2019)
The present case study focuses on identifying the problems that arise regarding the inadequate inventory management in the “Representations Soria” company, located in the city of Babahoyo. The main findings in the investigation, reflect that the organization does not have an automation of processes to manage the inventory efficiently, which generates inconsistencies in the counting and registration of the merchandise; This is due to the lack of technical application in inventory-related activities, since employees register goods and merchandise from empiricism, a situation that is not recommended for a company that wishes to achieve sustained business development. By not making use of a technological system or mechanism for inventory management, the company is subject to continuous errors, caused by manual registration; hence the importance given in this case study, to the need to generate a quality perspective, which includes proper planning and allocation of resources to improve the current situation regarding the weaknesses that the company presents. The conclusions presented based on the study carried out, indicate that the company “Representations Soria” does not have collaborators who have full competences in terms of efficient inventory management; In addition, the organization of the merchandise is not carried out optimally, due to the limited physical space that the company has